Sharia Digital Marketing as an Effort to Increase the Income of MSMEs in North Lombok Regency - Rezky Chikal Pratama; Zaenafi Ariani; Ahadiah Agustina (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Marketing through digital media has become a common step for MSME actors. This makes it easier for them to reach consumers, especially in the modern era when consumers can easily find the products they want. Digital marketing strategy is the key to improving and developing MSME businesses in a better direction in the future. This study uses a descriptive qualitative research method with data collection and analysis techniques involving observation, interviews, and the use of secondary data such as journals, articles, books, and related mass media. The data analysis technique used is Miles and Huberman analysis, which includes data collection, data reduction, data presentation, and drawing conclusions or verification. The results of the study show that digital marketing to MSMEs in Tanjung District has used various applications such as WhatsApp, Instagram, TikTok, and Facebook. The use of these applications is very helpful in increasing product marketing, not only among local people but also reaching consumers from various regions. However, the scope of digital marketing has a positive impact although it may not always be in accordance with expectations.